2020
DOI: 10.1038/s41467-020-14354-5
|View full text |Cite
|
Sign up to set email alerts
|

Programmable meroterpene synthesis

Abstract: The bicyclo[3.3.1]nonane architecture is a privileged structural motif found in over 1000 natural products with relevance to neurodegenerative disease, bacterial and parasitic infection, and cancer among others. Despite disparate biosynthetic machinery, alkaloid, terpene, and polyketide-producing organisms have all evolved pathways to incorporate this carbocyclic ring system. Natural products of mixed polyketide/terpenoid origins (meroterpenes) are a particularly rich and important source of biologically activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 77 publications
1
27
0
Order By: Relevance
“…In the course of chemical studies on PPAPs of Garcinia subelliptica (Guttiferae) [ 128 , 129 ], we found that garsubellin A ( 71 ) could increase the ChAT activity, a key enzyme for physiologic acetylcholine synthesis in the nervous system, by up to 154% at 10 μM in comparison with the control in primary cultured P10 rat septal neurons [ 130 ]. Owing to its important biological activity and architectural structure, garsubellin A ( 71 ) stimulated substantial synthetic effort, and the excellent synthetic achievements have been reported [ 127 , 131 133 ]. More efficient synthetic methods of 71 , however, still have to be developed to supply sufficient quantities to explore its full biological characterization (Figs.…”
Section: Miscellaneous Natural Products With Neurotrophic Effectsmentioning
confidence: 99%
“…In the course of chemical studies on PPAPs of Garcinia subelliptica (Guttiferae) [ 128 , 129 ], we found that garsubellin A ( 71 ) could increase the ChAT activity, a key enzyme for physiologic acetylcholine synthesis in the nervous system, by up to 154% at 10 μM in comparison with the control in primary cultured P10 rat septal neurons [ 130 ]. Owing to its important biological activity and architectural structure, garsubellin A ( 71 ) stimulated substantial synthetic effort, and the excellent synthetic achievements have been reported [ 127 , 131 133 ]. More efficient synthetic methods of 71 , however, still have to be developed to supply sufficient quantities to explore its full biological characterization (Figs.…”
Section: Miscellaneous Natural Products With Neurotrophic Effectsmentioning
confidence: 99%
“…Phloroglucin-like natural products such as hyperforin ( Fig. 17 ), berkeleyone A, berkeleydione, huperzine, upia, mexicanolide, rugulosone, nemorosome, and garsubellin A, C, and D 99 have potential medicinal application in treating inflammation, depression, as well as neurologic disorders such as Alzheimer's disease.…”
Section: Pinene As Intermediate For Complex Natural Productsmentioning
confidence: 99%
“…From a practical point of view, in complex systems such as hydrated membranes, the scattering function is given by a few terms associated with the polymer (S P ) and water (S W ) dynamics, so that the scattering function can be expressed as: (10) .…”
Section: Ion Hopping and Water Diffusionmentioning
confidence: 99%
“…Critical issues that are currently being investigated address improvements in durability and performance efficiency combined with lowered production costs [5,6]. Research to develop and model the chemistry and improve the performance of novel as well as current membrane formulations is under way in laboratories worldwide [6][7][8][9][10]. Neutron scattering (NS) and imaging techniques designed to probe the structure and dynamics of bulk and thin film materials are playing an increasing role in studies to understand, control and develop critical issues of water uptake and management related to polymer structure, selective transport of ions and molecular species through the membrane, and the coupling between these dynamic processes.…”
Section: Introductionmentioning
confidence: 99%